2022
DOI: 10.3389/fmicb.2021.758144
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Cadmium (Cd) Tolerance in Newly Isolated Bacterial Strain, Ochrobactrum intermedium BB12, and Its Role in Alleviation of Cd Stress in Spinach Plant (Spinacia oleracea L.)

Abstract: A cadmium (Cd)–tolerant bacterium Ochrobactrum intermedium BB12 was isolated from sewage waste collected from the municipal sewage dumping site of Bhopal, India. The bacterium showed multiple heavy metal tolerance ability and had the highest minimum inhibitory concentration of 150 mg L–1 of Cd. Growth kinetics, biosorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared (FTIR) spectroscopy studies on BB12 in the presence of Cd suggested biosorption as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 107 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Parallelly, the work done by Renu et al (2021) concluded that heavy metal tolerant bacterial strains like MB1, RD4, MF7, and MC4 promoted the growth of spinach plants in terms of root and shoot length, fresh and dry root weight, and shoot weight in the presence of heavy metals like arsenic, chromium, nickel, and lead and also reduced the heavy metal toxicity in spinach. Also, the findings of Renu et al (2022) concluded that inoculation of Cd‐tolerant bacterium Ochrobactrum intermedium BB12 in spinach plants under Cd stress conditions, showed increased germination, increased chlorophyll content, and increased shoot (28.33%) and root fresh weight (72.60%) at 50 mg/kg of cadmium concentration after 75 days of sowing.…”
Section: Discussionmentioning
confidence: 94%
“…Parallelly, the work done by Renu et al (2021) concluded that heavy metal tolerant bacterial strains like MB1, RD4, MF7, and MC4 promoted the growth of spinach plants in terms of root and shoot length, fresh and dry root weight, and shoot weight in the presence of heavy metals like arsenic, chromium, nickel, and lead and also reduced the heavy metal toxicity in spinach. Also, the findings of Renu et al (2022) concluded that inoculation of Cd‐tolerant bacterium Ochrobactrum intermedium BB12 in spinach plants under Cd stress conditions, showed increased germination, increased chlorophyll content, and increased shoot (28.33%) and root fresh weight (72.60%) at 50 mg/kg of cadmium concentration after 75 days of sowing.…”
Section: Discussionmentioning
confidence: 94%
“…Shehzadi et al [106] isolated cultivable endophytic bacteria from the shoots and roots It is known that the versatile Pseudomonas genus can tolerate HMs because of its ability to adapt to various environmental conditions [108,109]. Ochrobactrum strains have been shown to alleviate Cd toxicity in spinach (Spinacia oleracea L.) [110] and rice (Oryza sativa) [111] and adsorb Cd and Cr in their cell wall due to exopolysaccharides content [112][113][114]. Similarly, some Acinetobacter strains have been applied to improve the removal efficiency of heavy metals such as Cr [115][116][117], while Alcaligenes has been reported to be tolerant to Cd, Cu, Ni, Zn, and Cr [118,119].…”
Section: Bacterial Communities Associated With the Roots Of Typha Exp...mentioning
confidence: 99%
“…Similarly, Pirzadah et al (2018) investigate the effect of Hg on oxidative stress in plants not inoculated with PGPB, finding similar results to those described in the present work. The effect that PGPB inoculation induces the decrease of ROS is known (Heidari and Golpayegani, 2012;Morcillo and Manzanera, 2021) in substrates contaminated by different heavy metals: Hg (Pirzadah et al, 2018), Pb (Abdelkrim et al, 2018), Cu (Fatnassi et al, 2015), Zn (Islam et al, 2014), and Cd (Azimychetabi et al, 2021;Renu et al, 2022). The PGPB species commonly used are those belonging to the genus Bacillus (Vardharajula et al, 2011;Moreno-Galván et al, 2020) and Pseudomonas (Sandhya et al, 2010).…”
Section: Antioxidative Defense Enzymesmentioning
confidence: 99%